A recepção dos mashups literários nacionais: uma análise discursiva de representações do leitor jovem - Conti, Clarissa Neves (Universidade Federal de São Carlos, 2016)
In recent years, we have noticed the appearance of special genres of fictional narratives, such as literary mashups. The emergence of such narratives is partly due to certain changes caused in writing and reading practices by new technologies of production and reception of texts. Literary mashups are characterized by their hybrid nature and the desecrated manner that it relates to culture canons. They find their roots on some “remix culture” principles, such as the articulation between “high” and “low” culture, erudition and pop. Their originality may be found exactly in the unexpected aspect of such combination. In despite of being a worldwide editorial phenomenon, this kind of books does not seem to have accomplished similar success in Brazilian market. In Brazil, literary mashups segment does not have a numerous quantity of titles, and yet they might be still an important source to describe contemporary representations of Brazilian youth reading practices. This type of narratives has been built under an international successful publishing model, and they have been introduced as a fun and playful way of bringing young readers close to the greatest classics of literature. Therefore, by means of analyzing the methods of diffusion and reception of literary mashups in Brazil, we seek to promote an analysis of the discourses about reading that support such publishing project. By doing so, we intend to identify and describe how those discourses are manifested on language, that is, how writing strategies used on the books and readers impressions about the books create a representation of both literature and their readers. Our research corpus was built by Brazilian mashup works and by a collection of utterances which have been selected from young readers comments posted on literary blogs, notes and advertisements made on the news by journalists and professional critics. For this purpose, we take as a basis the Discourse Analysis theory articulated with principles of Cultural History of Reading, with the aim of expand our view on the publishing strategies which were applied on the construction of mashup books and how those strategies may be a sign of representations of their intended readers. As a result, we could have some clues of the discoursive representations built about young readers and their reading practices, such as the reinforcement of a discourse that make canon texts sacred, for what it refuses any interference that could destroy the quality of the classic literary work.
Brazilian literary mashups: a discourse analysis of young readers representations
Keywords: Análise de discurso; História cultural; Leitor jovem; Mashups literários; Discourse analysis; Representations of readers; Young readers; Literary mashups; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA